A comparative study of demographical and clinical characteristics on the level of pain severity - Sekeon, Sekplin A. S.; Mawuntu, Arthur H. P. (International Journal of Research in Medical Sciences, 2020)
Background: Pain is one of the global public health challenges. Pain is not only contributing to physical complaint but also mental and personality dimension as well as productivity issues. Severity of pain is affected by multiple factors, including biological, psychological, and social factors. The objective of the study was to analyse whether there is difference of severity level of pain among several demographical and clinical characteristics of patients with pain. Methods: A hospital-based observational study was conducted with cross-sectional design for six months period. Population of research were patients with pain as the chief complaint treated at the neurology outpatient clinic. Eligible sample were obtained through consecutive total sampling technique. The difference of severity of pain (mild/moderate/severe) and 6 characteristics of patients (age group, sex, number of morbidities, body area of pain, onset and working diagnosis) were analysed. Chi square statistical analysis with SPSS version 17.0 was employed with p value <0,05 were regarded as significant level. Results: Majority of patients were female (58.8%), in the 51-60 age group, at senior high school level and living in urban area. Almost half of the patients with pain have no history of comorbidity (45.9%), which relatively almost equal with patients with single comorbidity. Three mostly affected body areas were shoulder, wrist, and lower back. Majority of patients admitted with moderate level of pain. The onset of pain was mostly above 6 months before visiting the clinic. During the study period, the most frequently working diagnosis were carpal tunnel syndrome and osteoarthritis knee. In bivariate analysis, we found that among 6 demographical and clinical characteristics, body area of pain and working diagnosis have significant difference associated with severity of pain (p value<0.05). Conclusions: There is significant difference of severity of pain based on body area of pain and working diagnosis. We could not detect significant difference of severity of pain based on age group, sex, number of comorbidity and onset of pain.